GENERATIVE AI AS A NOVEL PROBLEM SOLVING TOOL FOR INVESTMENT BANKING: AN EXPLORATORY STUDY - Shimpi, Leena Sharad; Srivastava, Saksham Kumar; Singh, Nidhi; Srivastava, Raman (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The use of AI in the banking industry has been growing rapidly, transforming various aspects of banking operations. The extent of AI adoption in the banking sector is significant and encompasses a wide range of applications. Artificial Intelligence (AI) refers to the simulation of human intelligence in machines that are programmed to think, learn, and perform tasks that typically require human intelligence. The goal of AI is to create systems that can perform tasks that would normally require human intelligence, such as visual perception, speech recognition, decision-making, language translation, and problem-solving. The extent of AI adoption varies among banks, but the trend is towards increased integration of AI technologies to improve efficiency, customer experience, and decision-making processes. Adoption of AI has helped the banking industry to improve their process and streamline the operations. Customer service time has reduced substantially. Client service processes has improved and the decision making is faster.